Contemporaneous International Asthma Guidelines Present Differing Recommendations: An Analysis. (23rd June 2016) - Gupta, Samir; Paolucci, Emily; Kaplan, Alan; Boulet, Louis-Philippe
Abstract : Background . Several international groups develop asthma guidelines. Conflicting recommendations across guidelines have been described in several disease areas and may contribute to practice variability. Accordingly, we compared the latest Canadian Thoracic Society (CTS) asthma guideline with contemporaneous international asthma guidelines to evaluate conflicting recommendations and their causes. Methods . We identified the latest CTS asthma guideline update (2012) and the following societies which also updated their guidelines in 2012: the British Thoracic Society and Scottish Intercollegiate Guidelines Network and the Global Initiative for Asthma. We compared these three guidelines on (1) key methodological factors and (2) adult pharmacotherapy recommendations. Results . Methods used and documentation provided for literature search strategy and dates, evidence synthesis, outcomes considered, evidence appraisal, and recommendation formulation varied between guidelines. Criteria used to define suboptimal asthma control varied widely between guidelines. Inhaled corticosteroid dosing recommendations diverged, as did recommendations surrounding use of budesonide/formoterol as a reliever and controller and recommendations in the subsequent step. Conclusions . There are important differences between recommendations provided in contemporaneous asthma guidelines. Causes include differences in methods used for interpreting evidence and formulating recommendations. Adopting a common set of valid and explicit methods across international societies could harmonize recommendations and facilitate guideline implementation.